Theoretical and Methodological Framework for Constructing Indicators for the Development of “Smart” Sustainable Cities in Ukraine: The Topic “Economy” - Korepanov, О. S. (Statistics of Ukraine, 2017)
The article’s objective is to create a theoretical and methodological framework for constructing indicators of the development of “smart” sustainable cities, in order to build a scientifically grounded information base for elaborating the national strategy for the development of “smart” sustainable cities in Ukraine. A review of the set of standardized indicators for “smart” sustainable cities by ISO 37120:2014 “Sustainable development of communities - Indicators for city services and quality of life” is made, to ensure a complex and integral approach to the sustainable development and viability of territorial communities, which enables for making cross-city comparisons, developing innovative visualizations and conducting individual analysis of development tendencies;. . 17 broader topics are examined in the article, by which indicators in ISO 37120 are grouped. Special attention is drawn to main and auxiliary indicators of municipal services and quality of life in the topic “Economy”. The nomenclature of these indicators and their computation algorithm by ISO 37120 is given. The essential meaning of the main indicators used for computation of the above mentioned indicators is shown. A preliminary analysis of statistical information structured by ISO 37120, which is collected by cities of the world and displayed by the World Council on City Data on the Open City Data Portal, is made. The main principles and the procedure for certification of cities by ISO 37120, which was first constructed and implemented by the World Council on City Data as the world leader in standardized indicators, are highlighted. After the certification, the cities are included to the Global Cities Registry™. The cities of the world registered in the Global Cities Registry™ in 2014-2017, which provided complete data on the topic “Economy”, by main and auxiliary indicators, are grouped by the author using various algorithms of cluster analysis. The conclusions on the overall economic development of the city groups are made on the basis of the computed average values of the normalized characteristics of economic indicators The conclusions are confirmed by visual analysis of a radial diagram of the main and auxiliary indicators on the topic “Economy” for the cities represented in each cluster: Amsterdam, Barcelona, Buenos-Aires, Melbourne, and Los-Angeles.